PENGARUH BIAYA PRODUKSI DAN HARGA JUAL TERHADAP LABA BERSIH (STUDI KASUS PADA BURSA EFEK INDONESIA) - Seftianty, Carolita (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
This study aims to determine the effect of production cost and selling price to net income on PT.Kimia Farma (Persero) Tbk is listed on the Bursa Efek Indonesia. The variables used in this study is the production cost, selling price and net income. The sample used is the quarterly financial statements on PT. Kimia Farma (Persero) Tbk with the period 2005-2012, the number of samples in this study there were 32 samples. The analysis used is multiple linear regression. Analysis was used to determine significant either partially or simultaneously. Partial test results stating that tcount> t table (3.771> 2.024) and 0.01 significance value <0.05, which means that Ho is rejected, then the partial cost of production has a significant effect on net income at PT. Kimia Farma (Persero) Tbk. Partial test results stating that tcount> ttable (-2.778 <2.024) and a significant value of 0.09> 0.05, which means that Ho is accepted, then the partial sale price there is no significant effect on net income at PT. Kimia Farma Tbk. The test results simultaneously stating that Fhitung> F (59.947> 3.224) and the significance value 0.000 <0.05, which means that Ho is rejected, it means the simultaneous production costs and selling prices have a significant effect on net income at PT. Kimia Farma (Persero) Tbk.